Предмет: Алгебра,
автор: nastenafeskova
Представьте в виде многочлена:
(a+b)(a-b)(a^2+b^2)
Упростите выражение:
с(с-2)(с+2)-(с-1)(с^2+c+1)
Разложите на множители многочлен:
2x+2y-x^2-2xy-y^2
Ответы
Автор ответа:
0
1)(a+b)(a-b)(a²+b²)=(a²-b²)(a²+b²)=aˇ4 - bˇ4
2)c(c-2)(c+2)-(c-1)(c²+c+1)=c(c²-4)-(c³-1)=c³-4c-c³+1=-4c+1
3)2x+2y-x²-2xy-y²=2(x+y)-(x²+2xy+y²)=2(x+y)-(x+y)(x+y)=
=(x+y)(2-x-y)
2)c(c-2)(c+2)-(c-1)(c²+c+1)=c(c²-4)-(c³-1)=c³-4c-c³+1=-4c+1
3)2x+2y-x²-2xy-y²=2(x+y)-(x²+2xy+y²)=2(x+y)-(x+y)(x+y)=
=(x+y)(2-x-y)
Похожие вопросы
Предмет: Русский язык,
автор: una2472
Предмет: Алгебра,
автор: denisrazapov421
Предмет: Русский язык,
автор: samalakaeva
Предмет: Литература,
автор: света338866